2011
DOI: 10.3389/fpls.2011.00096
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis 14-3-3 Proteins: Fascinating and Less Fascinating Aspects

Abstract: 14-3-3 Dimers are well known to interact with diverse target proteins throughout eukaryotes. Most notably, association of 14-3-3s commonly requires phosphorylation of a serine or threonine residue within a specific sequence motif of the client protein. Studies with a focus on individual target proteins have unequivocally demonstrated 14-3-3s to be the crucial factors modifying the client’s activity state upon phosphorylation and, thus, finishing the job initiated by a kinase. In this respect, a recent in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 42 publications
0
63
0
Order By: Relevance
“…INTRODUCTION 14-3-3 proteins (14-3-3s) are phosphopeptide-binding proteins, which are highly conserved across eukaryotic cells including animals, plants and yeast (Roberts, 2003;Aitken, 2006;Jaspert et al, 2011). In Arabidopsis, there are a total of thirteen 14-3-3 genes predicted to encode functional proteins (Chevalier et al, 2009;Paul et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…INTRODUCTION 14-3-3 proteins (14-3-3s) are phosphopeptide-binding proteins, which are highly conserved across eukaryotic cells including animals, plants and yeast (Roberts, 2003;Aitken, 2006;Jaspert et al, 2011). In Arabidopsis, there are a total of thirteen 14-3-3 genes predicted to encode functional proteins (Chevalier et al, 2009;Paul et al, 2012).…”
mentioning
confidence: 99%
“…In Arabidopsis, there are a total of thirteen 14-3-3 genes predicted to encode functional proteins (Chevalier et al, 2009;Paul et al, 2012). Numerous studies have revealed that plant 14-3-3s participate in the regulation of diverse biological and physiological processes, including primary metabolism, stress response, membrane transport and signal transduction cascades (Chevalier et al, 2009;Jaspert et al, 2011;Paul et al, 2012;de Boer et al, 2013). 14-3-3s act through direct interactions with target proteins, including transcription factors, metabolic enzymes, signaling components and ion channel proteins (Kanamaru et al, 1999;Bai et al, 2007;Gampala et al, 2007;Ryu et al, 2007;Li et al, 2012;Yoon and Kieber, 2013;Catala et al, 2014).…”
mentioning
confidence: 99%
“…Furthermore, 14-3-3 proteins interact with the tonoplast potassium channel, TPK1, and strongly activate potassium transport activity [36,37]. Recently, it has been suggested that 14-3-3 proteins bind to mineral transporters including Zn, Mg, and Ca transporters [38,39,40,41]. Therefore, 14-3-3 proteins may play a role in nutrient accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…In the Arabidopsis genome, six genes that encode ACOs were identified in silico by Babula et al (2006). Recently, ACO2 and ACO4 proteins were found, which may interact with 14-3-3 proteins in a yeast two-hybrid system (Jaspert et al , 2011). Together with the present results, this indicates that 14-3-3 proteins may regulate the ethylene biosynthesis pathway by modulating ACS and ACO proteins.…”
Section: Discussionmentioning
confidence: 99%